Efisiensi Abu Terbang PLTU Sebagai Adsorben Dalam Menurunkan Kadar Fosfat Pada Limbah Cair Laundry - Nur Alfiah Putri Indarti (Fakultas Teknik, 2025)
Laundry wastewater contains phosphate levels up to 16.74 mg/L and may cause eutrophication without proper treatment. Adsorption using NaOH-activated fly ash is selected as an effective method to reduce phosphate levels. This study evaluated adsorption efficiency, kinetic models, and the effect of adsorbent mass and contact time. Batch method was used with adsorbent masses of (0, 1, 3, and 5 grams) and contact times of (15, 30, 45, 60 and 75 minutes). The highest phosphate removal efficiency reached 99.28% at 5 grams adsorbent and 45 minutes contact time. Phosphate levels were analyzed using UV-Vis spectrophotometry based on the ascorbic acid method. Data were analyzed using linear regression. The most suitable kinetic model was zero-order with R² close to 1 under optimum conditions. NaOH activation increased surface area and adsorption capacity, but also raised pH due to alkaline ions. Activated fly ash is effective as an alternative adsorbent for environmentally friendly laundry wastewater treatment.
Reuplod Repository Ratna 14 Juli 2026 Validasi dan Finalisasi Ratna 14 Juli 2026
Keywords: Coal fly ash; adsorption bacth; phosphate; reaction kinetics; NaOH activation; UV-Vis; zero-order kinetics; regression; Grey water.